Drilling Glacial Deposits in Offshore Polar Regions. Issue 31 (5th August 2014) - Hanebuth, Till J. J.; Rebesco, Michele; Urgeles, Roger; Lucchi, Renata G.; Freudenthal, Tim
<x xml:space="preserve">Abstract</x> High latitudes are of fundamental importance in the Earth's climate system—they house ice sheets that govern global sea level heights, influence how much solar energy is reflected back to space, and create deep and bottom waters that drive the ocean's ability to circulate energy and nutrients across the globe.